Analisis Kebutuhan dan Ketersediaan Air Domestik Menggunakan Metode Regresi di Kota Bogor - Virssa Noperissa; Roh Santoso Budi Waspodo (Departemen Teknik Sipil dan Lingkungan, IPB University, 2018)
Abstract : Increasing of population in a region is directly proportional to its development. Large number of populations resulted in the wider construction of residential areas. Construction of residential areas requires a clean water supply to fulfill households water demand. The purpose of this research were to analyze the domestic water demand and water availability in Bogor City, and to analyze the suitability between the domestic water supply and demand in Bogor City. The research was done from February to May 2018. This research needed data of population, hydrogeological map and annual river discharge. The correlation between population to domestic water demand using regression method was showed with equation Y = 19549X + 801520. In 20 years ahead domestic water demand will 80,328,688.57 m3 and total water demand will 125,312,754.2 m3, while total surface water availability will 174,078,720 m3/year. Domestic water availability in Bogor would decrease and would make clean water shortage after 2049 when population reached 1,720,323 persons. Keyword : domestic, surface water, water demand, water supply.